Management Model of Kitab Kuning Reading Acceleration Program at Mambaul Ulum Islamic Boarding School, Bira Timur Sampang - Sayyi, Ach.; Subhan, Moh; Al-Manduriy, Shahibul Muttaqien; Rofiqi, Rofiqi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
This research was motivated by the researchers' interest in the management of kitab kuning reading acceleration program at the Maktuba Mambaul Ulum Islamic boarding school, East Bira. The management carried out resulted in something extraordinary, where students who were still on average 7-12 years old managed to take part in the acceleration program for mastering the kitab kuning and master a series of other Islamic disciplines in just 2 years. If we relate to psychological theories, this is certainly a remarkable thing, considering that at their age in general they still live in the world of playgroup and education in the family. However, this does not make the management carried out ineffective, in fact this institution is able to create a pleasant learning atmosphere, and the target of this program can be achieved properly. This study focuses on the implementation of the kitab kuning reading acceleration program and its management in the pesantren. This research uses a qualitative approach and the type is descriptive research. As in the qualitative approach in general, the data collection techniques used are interviews, observation, and documentation. Analysis of the data used is by reduction, display, and verification. The research results show; first, the implementation of the acceleration program is by grouping students into 5 to 10 small groups with direct guidance for 24 hours by a musyrif. The two managements of kuning kuning reading acceleration program at the pesantren were carried out effectively and very well through planning, organizing, directing, and supervising carried out by this institution.